The Influence of Brand Orientation to Donation Intention with Attitude toward Charity as Mediator - Ramayanti, Ramayanti (JURNAL BISNIS STRATEGI, 2025)
This study aims to investigate the impact of brand orientation's dimensions (orchestration, interaction, and affect) on attitudes towards charity and donation intentions. Additionally, it explores whether attitudes towards charity mediate the relationship between orchestration, interaction, affect, and donation intentions. The sample consists of Indonesian residents who have interacted with and/or donated to non-profit organizations in Indonesia. Purposive sampling was used, resulting in a sample size of 282 participants. The data analysis method employed is Structural Equation Modeling (SEM) with Partial Least Squares (PLS) measurements. The research achieved a confidence level of 95%. Findings indicate that the Orchestration dimension has no direct or indirect influence on donation intentions through attitudes towards charity. However, both the Interaction and Affect dimensions directly and indirectly influence donation intentions, with attitudes towards charity serving as a mediator. The mediation effect obtained is weak so that the mediation that occurs is partial mediation.